2001
DOI: 10.1095/biolreprod64.5.1460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Stanozolol Treatment on Puberty in Female Rats1

Abstract: The effects of anabolic-androgenic steroid (AAS) abuse on the onset of puberty in female adolescents are largely unknown. This study assessed the acute effects of one AAS, stanozolol, on pubertal onset in the female rat. A single injection of stanozolol (5 mg/kg) on Postnatal Day (PN) 21 advanced vaginal opening but did not alter the onset of vaginal estrus. Higher doses of stanozolol treatment (10 and 25 mg/kg) also advanced vaginal opening but had no effect on vaginal estrus. The advancement of vaginal openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…ST increased the MTT value and PCNA expression in cultured growth plate chondrocytes, and these effects were not affected by an AR blocker. Previous studies have found that ST can cause vaginal peripheral precocious puberty of rats and open the vagina prematurely, but it did not interfere the estrous cycle (24) ; this effect can be blocked by the specifi c estrogen receptor inhibitor ICI182.780. It was proposed that in the reproductive tract, ST can activate the estrogen receptor pathway and play a role in inducing peripheral precocious puberty, although it cannot be aromatized to estrogen.…”
Section: Discussionmentioning
confidence: 89%
“…ST increased the MTT value and PCNA expression in cultured growth plate chondrocytes, and these effects were not affected by an AR blocker. Previous studies have found that ST can cause vaginal peripheral precocious puberty of rats and open the vagina prematurely, but it did not interfere the estrous cycle (24) ; this effect can be blocked by the specifi c estrogen receptor inhibitor ICI182.780. It was proposed that in the reproductive tract, ST can activate the estrogen receptor pathway and play a role in inducing peripheral precocious puberty, although it cannot be aromatized to estrogen.…”
Section: Discussionmentioning
confidence: 89%
“…The suppressive effect of stanozolol on aggression in the absence of provocation (Figure 1c) has been observed in both adolescent and adult rats, as well as in adult mice [1,30,31], underscoring the importance of the identity and chemical nature of any individual AAS in its behavioral actions. Although a correlation exists between the relative binding affinities of several AAS to the androgen receptor (AR) and their ability to elicit inter-male aggression, there is no simple relationship between AR affinity, AR binding and behavioral effects [29,32]; the suppressive effects of stanozolol may reflect the actions of this AAS at the estrogen receptor (ER) [33], as much as its low affinity at the AR.…”
Section: The Behavioral Effects Of Aas On Aggressionmentioning
confidence: 99%
“…In addition to AR-mediated actions, the AAS can also impose important biological actions via estrogen receptor alpha (ERα) and ERβ, either directly (24) or following aromatization (2528), as well as directly via progestin receptors (29). Beyond their interactions with these classical nuclear hormone signaling pathways, the AAS can elicit rapid effects through interactions with a non-AR/ER microsomal binding site (30), by allosteric regulation of enzymes involved in the biotransformation of steroids (20, 27, 31, 32), and by allosteric modulation of ion channels (33).…”
Section: Anabolic Androgenic Steroidsmentioning
confidence: 99%